The new turkey : the quiet revolution on the edge of europe - Morris, Chris ([S.l.] : Granta Books, 2005)
Turkey is a country in a state of flux, swept along by an extraordinary process of change. In the last few years a series of far-reaching political and economic reforms has swept away much of the old order which ruled the country for so long. Some people call it a second Turkish revolution. But resistance to reform remains strong. Pressure for change has come from ordinary people fed up with the old ways; it's also been motivated by the dominant issue of Turkish political life - the long pursuit of membership of the European Union. And yet Turkey remains a mystery to many outsiders; a complex country hard to understand. It's secular and Muslim, Western and Eastern, democratic and authoritarian, all at the same time. This book examines the potential and the problems of the new Turkey, and the expectations of the people who live there, drawing on first hand interviews and observations gathered over several years.